PENGARUH BEBAN KERJA DAN JAM KERJA TERHADAP KINERJA KARYAWAN DENGAN TURNOVER INTENTION SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PT RESTU ADHITAMA JAYASENTOSA - Abdul Wahab Mustagfirin (Jurnal Riset Multidisiplin Edukasi, 2026)
Employee performance is the work result achieved by employees in carrying out tasks according to their responsibilities and is influenced by factors such as workload, working hours, and turnover intention. This study aims to analyze the effect of workload and working hours on employee performance with turnover intention as an intervening variable among employees of PT Restu Adhitama Jayasentosa. The population consisted of 1,250 employees, while 130 respondents were selected using stratified random sampling based on length of service and the sample size guideline of at least five observations per indicator for Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected using a five-point Likert questionnaire and analyzed with SmartPLS 4 using the Embedded Two Stage Approach to test both the measurement and structural models. The results show that workload and working hours do not have a significant direct effect on employee performance, whereas working hours have a positive and significant effect on turnover intention, and turnover intention has a positive and significant effect on performance. Indirect effect analysis further indicates that turnover intention significantly mediates the relationship between working hours and performance, while the mediation effect of turnover intention on the link between workload and performance is not significant. Overall, the total effects of workload and working hours on performance are significant when turnover intention is considered as a mediating variable. These findings highlight the importance of managing working time and workload in tandem with effective turnover intention management strategies to sustain optimal employee performance in the manufacturing sector.